Comparative morphology of the epiphyses of Dilophonotini Burmeister, 1878 and Philampelini Burmeister, 1878 (Lepidoptera: Sphingidae) - Alcalde, Georgette Paola Ancajima (2021)
Hawkmoths occupy all regions of the globe, except Antarctica and Greenland. The family has 210 genera and about 1500 species, with about a third of the taxa registered for the Neotropical region. In Brazil, 33 genera and 196 species are known. They are classified into three subfamilies, with Macroglossinae being the most diverse lineage. They play an key in pollination. In this process, sphingids usually have contact with pollen grains in various parts of the body, particularly in the antennae. To clean them, these moths use the epiphyses that are in the foretibiae. In addition to being important for the biology of lepidopterans, the epiphysis also represents one of the synapomorphies that support the monophyly of these insects. However, few studies detail this structure morphologically. In this study, we seek to understand the possible variations in the epiphyses of representatives of Dilophonotini and Philampelini aiming to contribute to the discussions on the structure morphology, sexual dimorphism and the relationship with other body structures. For this, 19 genera and 59 species of both sexes (564 individuals in total) were studied. The extracted legs were placed in 10% KOH and taken to a water bath for four minutes to remove the scales. With the epiphyses cleaned, all individuals were photographed using a stereomicroscope and SEM to perform morphological descriptions of the epiphyses and measurements; after that, an allometric regression analysis was performed with other body structures (length and width of the epiphyses, position, length of the tibiae and length of the antennae); finally, an analysis of geometric morphometrics was conducted. As results, a new terminology was proposed for distinct parts of the epiphysis, 22 morphological characters were established from the epiphyses, greater morphological variation was found in the genera and subtribe levels, variations were found between males and females, a positive allometry was observed between the size of the epiphyses and the size of the antennae, and likewise, between the position of the epiphyses and the length of the tibiae. Morphometric analysis showed positive allometry, a homogeneous pattern with small variations between some genera. It was demonstrated that closely related genera have similar epiphyses, and others do not. This study is an important contribution to the knowledge of the Sphingidae morphology, with the proposal of new phenotypic characters for the group. In addition to being a detailed study of the epiphysis, a structure that has been historically neglected, it highlights the need to expand the comparative analysis to other groups of Lepidoptera for a better understanding of the importance of using the epiphysis morphology in the taxonomy of these insects, as well as for a better understanding of the variation and evolution of the structure and its associated antennal grooming behavior